STATISTICAL MECHANICS fundamentals and model solutions. - Dorlas, T. C. (Teunis Christiaan), 1955- ([S.l.] : CRC PRESS, 2021)
Statistical Mechanics: Fundamentals and Model Solutions, Second Edition Fully updated throughout and with new chapters on the Mayer expansion for classical gases and on cluster expansion for lattice models, this new edition of Statistical Mechanics: Fundamentals and Model Solutions provides a comprehensive introduction to equilibrium statistical mechanics for advanced undergraduate and graduate students of mathematics and physics. The author presents a fresh approach to the subject, setting out the basic assumptions clearly and emphasizing the importance of the thermodynamic limit and the role of convexity. With problems and solutions, the book clearly explains the role of models for physical systems, and discusses and solves various models. An understanding of these models is of increasing importance as they have proved to have applications in many areas of mathematics and physics. Features Updated throughout with new content from the field An established and well-loved textbook Contains new problems and solutions for further learning opportunity Author Professor Teunis C. Dorlas is at the Dublin Institute for Advanced Studies, Ireland.
OCLC-licensed vendor bibliographic record.
Keywords: Statistical mechanics; SCIENCE / Mechanics / General; SCIENCE / Mathematical Physics; MATHEMATICS / Probability & Statistics / General